Realidade mista e meio expositivo na arte contemporânea: insitu<>influxu - Casimiro, Giovanna Graziosi (2015)
This research in the field of theory and history of contemporary art, study configuration modes of Mixed Reality in the exhibition place and the consolidation of Exhibition Medium, structured by technological dynamics. Aims to discuss the cycle of relations among public<>artwork<>mediums presented as an explanation that how the elements of the Exhibition Medium works, and it‟s result is the dynamic insitu<>influx. The interactive artworks ARART and Extinction, the exhibition WeARinMoMA, the Krakow National Museum, the Museum of London and the project Talking Statues, contribute to think the specific conditions of an interactive Exhibition Medium, which dynamic create a constant transitions of power and sensibility. Emerging from the context of Art and Technology, applications of Mixed Reality are analyzed in institutional places, whose examples help to classify and understand how the space unfolds through many realities and the constant transition between the virtual and the physical dimension.